Fluid mechanics with engineering applications - Franzini, Joseph B. (McGraw-Hill, 1997)
This book is about: Properties of fluids; Fluid statics; Basics of fluid flow; Energy considerations in steady flow; Momentum and forces in fliud flow; ...